PENGARUH PENAMBAHAN SIMPLISIA DAUN STEVIA (Stevia rebaudiana) TERHADAP KARAKTERISTIK KIMIA DAN ORGANOLEPTIK JAMU INSTAN: The Effect of The Addition of Stevia Leaf Simplicia (Stevia Rebaudiana) On The Chemical and Organoleptic Characteristics of Instant Jamu - Siti Ariska Nur Cahyani, Rosiana Ulfa, Bagus Setyawan (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2022)
Instant herbal medicine is a food product in the form of a powder that is liked by almost all people from children to adults, in addition to the convenience of serving instant drinks, it is expected to provide benefits for body health. Stevia leaf is known as a low-calorie sweetener plant, the sweet taste is obtained from stevioside which is a glycoside composed of glucose, sucrose, and steviol. This study aims to determine the effect of the addition of stevia leaves on the chemical and organoleptic characteristics of instant herbal medicine. The experimental design used a completely randomized design (CRD) with 5 treatments consisting of P0 (control), P1 (5g stevia leaf), P2 (10g stevia leaf), P3 (15g stevia leaf), P4 (20g stevia leaf) and repeated in 4 times. The data obtained were analyzed using ANOVA and further tested with 5% DMRT. The results showed that the addition of stevia leaves had a very significant effect on the moisture content, and had a significant effect on the color, scent, taste, and viscosity of instant herbal medicine. Based on the results of ANOVA analysis, the moisturecontent was P1 with the addition of 5 grams of stevia leaves, and the results of the organoleptic test for color, scent, and taste that were preferred were P1 with the addition of 5 grams of stevia leaves, and for viscosity, the most preferred were P3 and P4 with the addition of stevia leaves. 15 grams and 20 grams.